2010
DOI: 10.1128/jvi.01077-10
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Residues in Virulent Canine Distemper Virus Hemagglutinin That Control CD150/SLAM-Binding Activity

Abstract: Morbillivirus cell entry is controlled by hemagglutinin (H), an envelope-anchored viral glycoprotein determining interaction with multiple host cell surface receptors. Subsequent to virus-receptor attachment, H is thought to transduce a signal triggering the viral fusion glycoprotein, which in turn drives virus-cell fusion activity. Cell entry through the universal morbillivirus receptor CD150/SLAM was reported to depend on two nearby microdomains located within the hemagglutinin. Here, we provide evidence tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 29 publications
3
54
0
Order By: Relevance
“…The residues within this region of CDV-H from the virulent A75/17 strain were replaced with alanine. Detection by flow cytometry of the C-terminally FLAG tagged H proteins (46) confirmed that all mutants except CDV-H I463A were properly expressed at the cell surface (not shown).…”
Section: Structure-guided Design Of Cdv-h Mutantsmentioning
confidence: 84%
See 4 more Smart Citations
“…The residues within this region of CDV-H from the virulent A75/17 strain were replaced with alanine. Detection by flow cytometry of the C-terminally FLAG tagged H proteins (46) confirmed that all mutants except CDV-H I463A were properly expressed at the cell surface (not shown).…”
Section: Structure-guided Design Of Cdv-h Mutantsmentioning
confidence: 84%
“…While residues interacting with SLAM in the morbillivirus H protein have already been mapped (17,38,40,46), two studies recently documented the identification of MeV-H residues responsible for promoting fusion activity in polarized epithelial cells (16,32). These clustered either near or within a recessed groove created by ␤-propeller blades 4 and 5 on one side of H (Fig.…”
Section: Structure-guided Design Of Cdv-h Mutantsmentioning
confidence: 99%
See 3 more Smart Citations